Disciplinarity and Literate Activity in Civil and Environmental Engineering: A Lifeworld Perspective. (October 2019) - Durst, Sarah
Too frequently, representations of disciplinary writing foreground static notions of knowledge creation and literate practice in science and engineering. Rooted in discourse community theory, such representations present normative tropes of scientific practice that background notions of disciplinarity and obscure people's lived experience and practice. Drawing on a case study of one woman, a civil and environmental engineer, this article argues for a lifeworld perspective of disciplinary becoming: a perspective that foregrounds notions of disciplinarity, lived experience, and literate practices as constantly mobile and in flux. The study suggests, specifically, that the woman's work as an engineer cannot be separated from the people with whom she works, or has worked, and that her development as a writer extends beyond typical accounts of disciplinary enculturation. The author concludes by offering implications of this research for studies of disciplinarity and school science.